The Effect of Mounting Height on GNSS Receiver Positioning Accuracy in Forest Conditions - Michał Zasada (Croatian Journal of Forest Engineering, 2014)
In spite of the high prices of GNSS receivers, many users decide to invest in this equipment because of the high accuracy of X, Y and Z data capture. Measurements in forested environments are affected by the increased positional error because of the signal multipath effect caused by trees. The main idea of this paper is to raise the antenna of a GNSS receiver during measurements, in order to reduce the multipath effect in the highest part of forests. A 15 meter pole was used in order to capture the GNSS signal at a height of 5, 10 and 15 m above ground level, in various forest conditions. The main factor, which determines the precision and accuracy, is the operational mode of the receiver. When in the FIXED mode, the results obtained are more reliable than those obtained when in the FLOAT mode. Due to difficult conditions in the forest stand, FIXED mode occurrence is not always possible, but much more likely at higher elevations. The FLOAT mode, however, is more likely to occur in the forest conditions and the obtained accuracy of the X and Y coordinates was ±0.81 m and 1.11 m for the elevation (Z coordinate). The best results were achieved for X and Y coordinates at an altitude of 10 m in a leafless state with an average error of ±0.54 m for the FLOAT mode. We cannot assume, therefore, that raising the GNSS antenna will improve the precision and accuracy in every case.